Heterogeneous Klebsiella pneumoniae Co-infections Complicate Personalized Bacteriophage Therapy - Qin, Jinhong; Wu, Nannan; Bao, Juan; Shi, Xin; Ou, Hongyu; Ye, Shanke; Zhao, Wei; Wei, Zhenquan; Cai, Jinfeng; Li, Lisha; Guo, Mingquan; Weng, Jingyan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Multidrug-resistant (MDR) organisms have increased worldwide, posing a major challenge for the clinical management of infection. Bacteriophage is expected as potential effective therapeutic agents for difficult-to-treat infections. When performing bacteriophage therapy, the susceptibility of lytic bacteriophage to the target bacteria is selected by laboratory isolate from patients. The presence of a subpopulation in a main population of tested cells, coupled with the rapid development of phage-resistant populations, will make bacteriophage therapy ineffective. We aimed to treat a man with multifocal urinary tract infections of MDR Klebsiella pneumoniae by phage therapy. However, the presence of polyclonal co-infectious cells in his renal pelvis and bladder led to the failure of three consecutive phage therapies. After analysis, the patient was performed with percutaneous nephrostomy (PCN). A cocktail of bacteriophages was selected for activity against all 21 heterogeneous isolates and irrigated simultaneously via the kidney and bladder to eradicate multifocal colonization, combined with antibiotic treatment. Finally, the patient recovered with an obviously improved bladder. The success of this case provides valuable treatment ideas and solutions for phage treatment of complex infections. Clinical Trial Registration www.chictr.org.cn, identifier ChiCTR1900020989.